Thermal properties of asphalt pavements under dry and wet conditions - Hassn, Abdushaffi; Chiarelli, Andrea; Dawson, Andrew; Garcia, Alvaro (Elsevier, 2016)
Air voids play an important role in the temperature evolution of asphalt pavements exposed to the sun's radiation and the environment, but their effects have never been precisely quantified before. The objective of this article is to understand and quantify the effect of air voids on the temperature evolution of asphalt mixture under dry and wet conditions. To achieve this objective, dry and saturated asphalt slabs with different air voids contents have been exposed to infrared light and the surface and bottom temperature evolution, heat flux and evaporation rate have been measured. It was observed that under dry conditions air voids simply affect the specific heat capacity and thermal conductivity of asphalt mixture, while under wet conditions the energy used by water for evaporation reduces drastically the temperature of asphalt mixture. This has significance for Urban Heat Island mitigation amongst other implications.